2013
DOI: 10.1603/ec12505
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition Efficacy of <I>Drosophila suzukii</I> (Diptera: Drosophilidae) on Different Cultivars of Blueberry

Abstract: Drosophila suzukii (Matsumura) is an important pest of thin-skinned fruits including blueberry, raspberry, strawberry, and cherry. Blueberry was introduced into Japan in the 1950s, and severe economic losses attributable to D. suzukii were first reported in 2002. The objective of this study was to elucidate whether oviposition behavior varies among blueberry cultivars having different firmness of fruit. Fruit firmness in 12 cultivars of highbush blueberry (Vaccinium corymbosum L.) and rabbiteye blueberry (Vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 10 publications
8
55
0
2
Order By: Relevance
“…However, there may be other factors that are influencing the infestation patterns observed. Consistent with other studies, we found that there are higher levels of infestations in some varieties, and that some varieties produced more larvae [1] [9] [25]. We also observed a significant negative correlation in both of these factors as the harvest season progressed.…”
Section: Discussionsupporting
confidence: 92%
“…However, there may be other factors that are influencing the infestation patterns observed. Consistent with other studies, we found that there are higher levels of infestations in some varieties, and that some varieties produced more larvae [1] [9] [25]. We also observed a significant negative correlation in both of these factors as the harvest season progressed.…”
Section: Discussionsupporting
confidence: 92%
“…Their research showed that no D. suzukii egg was deposited in the medium with the highest penetration force and brix level, but the relationship was not consistent across the four treatment levels measured. Lee et al (2011b) reported that the number of D. suzukii eggs increased as brix levels increased within tested berry cultivars and Kinjo et al (2013) reported that D. suzukii laid more eggs in blueberry cultivars that had softer rather than Þrmer fruit. Laboratory studies also showed that D. suzukii prefers ripening cherries to ripe ones and this may increase the chance of the larvae to fully develop and reach maturity before the fruit totally decays (Poyet et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies conducted on spotted wing drosophila conÞrm that the drosophilid can infest numerous fruit crops, most biological studies on D. suzukii have focused on cherry and berry crops (Mitsui et al 2006, Lee et al 2011b, Burrack et al 2013, Kinjo et al 2013, Tochen et al 2014. Previous studies suggest that many external (e.g., Þrmness) or internal (e.g., sugar content and pH values) fruit characteristics can affect the susceptibility of the fruit to D. suzukii (Mitsui et al 2006, Lee et al 2011b, Burrack et al 2013.…”
Section: Abstract Stone Fruit Peach Fuzz Indumenta Drosophila Suzmentioning
confidence: 99%
See 1 more Smart Citation
“…Estes autores observaram aumento gradativo do ataque da D. suzukii, associado à maturação de cultivares de videira e, principalmente, à diminuição da resistência à penetração da epiderme e de componentes ácidos, além da elevação dos teores de sólidos solúveis. Outros trabalhos sobre videira também mostraram que a resistência à penetração foi o principal fator ligado à suscetibilidade de uvas à D. suzukii, que responderam de forma negativa à oviposição (Lee et al, 2011;Burrack et al, 2013;Kinjo et al, 2013;Ioriatti et al, 2015). Porém, no atual trabalho, não se obteve correlação significativa entre esses fatores e o índice de ataque da D. suzukii.…”
Section: Genótipo Ovos Por Bagaunclassified